A Case of Polyarteritis Nodosa with Bilateral Ureteral Obstruction - Yoo, Bin (Korean J Intern Med, 1996)
We report a case of bilateral ureteral obstruction most likely caused by polyarteritis nodosa. The diagnosis was based upon muscle biopsy which showed typical necrotizing vasculitis in medium size artery in conjunction with microaneurysms in renal angiography. Ureteral obstruction is a rare manifestation of polyarteritis nodosa. This condition is thought to result from vasculitis of periureteral vessels. The patient was managed with prednisolone alone, which resulted in complete resolution of ureteral obstruction on both sides.